Aluminum disrupts the prenatal development of the male and female gerbil prostate (Meriones unguiculatus) - Gomes, Liana S.; Costa, Janaína R.; Campos, Mônica S.; Marques, Mara R.; Biancardi, Manoel F.; Taboga, Sebastião R. [UNESP]; Ghedini, Paulo C.; Santos, Fernanda C.A. (Elsevier, 2019)
Normal prostate development is highly dependent of an equilibrated hormonal regulation, so that sensible interferences during this period may predispose the gland to lesions during aging. Industrial activities have increased the exposure of this gland to active elements found in environment, such as aluminum (Al). Al presents toxic effect for living beings, having the potential to disrupt the development and growth of several organs and systems. Therefore, the aim of this study was to evaluate whether the prenatal exposure to Al may alter the development and morphophysiology of the gerbil prostate (Meriones unguiculatus). Pregnant females were orally exposed to aluminum chloride (100 mg/kg/day) from 17th to 21th gestational day. Following the birth, the male and female pups were euthanized with 1 (PN1) and 90-days-old (PN90). The prostates were collected for biometrical, three-dimensional reconstruction, morphometrical, stereological, and immunohistochemical analysis. Results indicated that Al decreases the body weight of PN1 males and females, and also reduce the anogenital distance of PN1 females. Moreover, Al changed the prostate developmental patterns of PN1 animals, causing an increase in proliferative status and decreasing androgen receptor immunostaining. The results suggest that Al-promoted changes were permanent, since low androgen receptor frequency, increased serum testosterone levels and high proliferation index were observed in adult gerbils. This study demonstrated that body and prostatic changes were more pronounced in females than in males, and that Al performed as an endocrine-disrupting chemical in gerbils.
Keywords: Androgen receptor; Antiandrogens; Estrogen receptor alpha; Female prostate; Metalloestrogen; Ventral prostate